2023
DOI: 10.1177/20552076231203902
|View full text |Cite
|
Sign up to set email alerts
|

Significance of platelet adhesion-related genes in colon cancer based on non-negative matrix factorization-based clustering algorithm

Xiao-jv Chi,
Yi-bei Song,
Deng-he Liu
et al.

Abstract: Background Although surgical methods are the most effective treatments for colon adenocarcinoma (COAD), the cure rates remain low, and recurrence rates remain high. Furthermore, platelet adhesion-related genes are gaining attention as potential regulators of tumorigenesis. Therefore, identifying the mechanisms responsible for the regulation of these genes in patients with COAD has become important. The present study aims to investigate the underlying mechanisms of platelet adhesion-related genes in COAD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…For example, Kcnd2, Tspan12, Ing3 and Cped1 located on Chromosome six are known to promote proliferation of breast cancer cells ( Yang et al, 2023 ), be a critical factor for cancer associated fibroblast mediated invasion ( Otomo et al, 2014 ), used as a potential biomarker for CRC/breast cancer ( Kim and Lee, 2022 ; Li et al, 2023 ) or confer oncogenic effects in prostate cancer ( Zhu et al, 2023 ) respectively. Likewise on chromosome 12, expression of Matn3, Osr1, and Nt5c1b have been associated with colon adenocarcinoma, gastric and breast cancer development ( Zhao Z. et al, 2023a ; Chi et al, 2023 ; Gadwal et al, 2023 ); potential use as a biomarker for breast cancer ( Li et al, 2020 ) or promotion of EMT and metastasis in breast cancer ( Wang et al, 2020 ; Li et al, 2021 ) and identified as a cancer testis-antigen in canine malignancies ( Nemec et al, 2019 ) respectively. On the X chromosome, Il13ra1, Pgrmc1, Septin6, Ndufa1, Nkrf, Zcchc12, Lonrf3, Slc25a5, Ct47 and Dock11 have been associated with numerous cancers including: breast cancer ( Park et al, 2017 ; Zhao Y. et al, 2023 ), basal cell carcinoma ( Mamelak et al, 2005 ), glioblastoma multiforme ( Han and Puri, 2018 ), gastric cancer ( Li et al, 2019 ), hepatocellular carcinoma ( Fan et al, 2021 ), lung cancer ( Lu et al, 2023 ), neuroblastoma ( Seneviratne et al, 2023 ), osteosarcoma ( Cui and Dong, 2022 ), ovarian serous cystadenocarcinoma ( Zhang et al, 2018 ), pancreatic cancer ( Feng et al, 2021 ; Shi et al, 2022 ), papillary thyroid cancer ( Wang et al, 2017 ) and T-cell acute lymphoblastic leukemia ( Lahera et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kcnd2, Tspan12, Ing3 and Cped1 located on Chromosome six are known to promote proliferation of breast cancer cells ( Yang et al, 2023 ), be a critical factor for cancer associated fibroblast mediated invasion ( Otomo et al, 2014 ), used as a potential biomarker for CRC/breast cancer ( Kim and Lee, 2022 ; Li et al, 2023 ) or confer oncogenic effects in prostate cancer ( Zhu et al, 2023 ) respectively. Likewise on chromosome 12, expression of Matn3, Osr1, and Nt5c1b have been associated with colon adenocarcinoma, gastric and breast cancer development ( Zhao Z. et al, 2023a ; Chi et al, 2023 ; Gadwal et al, 2023 ); potential use as a biomarker for breast cancer ( Li et al, 2020 ) or promotion of EMT and metastasis in breast cancer ( Wang et al, 2020 ; Li et al, 2021 ) and identified as a cancer testis-antigen in canine malignancies ( Nemec et al, 2019 ) respectively. On the X chromosome, Il13ra1, Pgrmc1, Septin6, Ndufa1, Nkrf, Zcchc12, Lonrf3, Slc25a5, Ct47 and Dock11 have been associated with numerous cancers including: breast cancer ( Park et al, 2017 ; Zhao Y. et al, 2023 ), basal cell carcinoma ( Mamelak et al, 2005 ), glioblastoma multiforme ( Han and Puri, 2018 ), gastric cancer ( Li et al, 2019 ), hepatocellular carcinoma ( Fan et al, 2021 ), lung cancer ( Lu et al, 2023 ), neuroblastoma ( Seneviratne et al, 2023 ), osteosarcoma ( Cui and Dong, 2022 ), ovarian serous cystadenocarcinoma ( Zhang et al, 2018 ), pancreatic cancer ( Feng et al, 2021 ; Shi et al, 2022 ), papillary thyroid cancer ( Wang et al, 2017 ) and T-cell acute lymphoblastic leukemia ( Lahera et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%